Antibacterial activity and mechanism of three isomeric terpineols of Cinnamomum longepaniculatum leaf oil - Huang, Jinfeng; Yang, Liyan; Zou, Yue; Luo, Sican; Wang, Xin; Liang, Yujuan; Du, Yonghua; Feng, Ruizhang; Wei, Qin (Folia microbiologica, 2021)
α-Terpineol, terpinen-4-ol, and δ-terpineol, isomers of terpineol, are among the compounds that give Cinnamomum longepaniculatum leaf oil its distinguished pleasant smell. The objective of this study was to evaluate the antimicrobial activity of these three isomeric terpineols. The determination of antibacterial activity was based on the minimum inhibition concentration (MIC) and minimum bactericide concentration (MBC). Changes in time-kill curve, alkaline phosphatase (AKP), UV-absorbing material, membrane potential, and scanning electron microscopy (SEM) were measured to elucidate the possible antimicrobial mechanism. α-Terpineol, terpinen-4-ol, and δ-terpineol demonstrated good inhibitory effects against several gram-negative bacteria, particularly Shigella flexneri. MIC and MBC of α-terpineol and terpinen-4-ol were similar (0.766 mg/mL and 1.531 mg/mL, respectively) for S. flexneri, while the MIC and MBC values of δ-terpineol were 0.780 mg/mL and 3.125 mg/mL, respectively. Time-kill curves showed that the antibacterial activities of the tested compounds were in a concentration-dependent manner. Release of nucleic acids and proteins along with a decrease in membrane potential proved that α-terpineol, terpinen-4-ol, and δ-terpineol could increase the membrane permeability of Shigella flexneri. Additionally, the release of AKP suggested that the cell wall was destroyed. SEM analysis further confirmed that S. flexneri cell membranes were damaged by α-terpineol, terpinen-4-ol, and δ-terpineol. Our research suggests that these three isomeric terpineols have the potential of being used as natural antibacterial agents by destroying the cell membrane and wall, resulting in cell death. However, the specific antibacterial activity differences need further investigation.
Keywords: membránové potenciály; mikrobiální testy citlivosti; terpeny; listy rostlin; oleje prchavé; Terpenes; Gram-Negative Bacteria; Anti-Bacterial Agents; Plant Leaves; isomerie; Oils, Volatile; Microbial Sensitivity Tests; gramnegativní bakterie; Isomerism; buněčná stěna; Cinnamomum; antibakteriální látky; skořicovník; Cell Wall; Membrane Potentials